Defect Process, Dopant Behaviour and Li Ion Mobility in the Li2MnO3 Cathode Material - Navaratnarajah Kuganathan (Energies, 2019)
Lithium manganite, Li2MnO3, is an attractive cathode material for rechargeable lithium ion batteries due to its large capacity, low cost and low toxicity. We employed well-established atomistic simulation techniques to examine defect processes, favourable dopants on the Mn site and lithium ion diffusion pathways in Li2MnO3. The Li Frenkel, which is necessary for the formation of Li vacancies in vacancy-assisted Li ion diffusion, is calculated to be the most favourable intrinsic defect (1.21 eV/defect). The cation intermixing is calculated to be the second most favourable defect process. High lithium ionic conductivity with a low activation energy of 0.44 eV indicates that a Li ion can be extracted easily in this material. To increase the capacity, trivalent dopants (Al3+, Co3+, Ga3+, Sc3+, In3+, Y3+, Gd3+ and La3+) were considered to create extra Li in Li2MnO3. The present calculations show that Al3+ is an ideal dopant for this strategy and that this is in agreement with the experiential study of Al-doped Li2MnO3. The favourable isovalent dopants are found to be the Si4+ and the Ge4+ on the Mn site.